Dependence of the Values of Inter-Component Phase Relations of the Harmonic Components of Vibration on the Displacement of Misaligned Shafts - D. A. Kechik; I. G. Davydov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The analytical dependence of the phases and values of intercomponent phase relations of the harmonic components of vibration displacement of misaligned shafts on their displacement has been presented in the article. Harmonic vibrations of the shafts were modeled using a Lagrangian connecting vibration displacement and forces acting in the system. For ease of derivation, the Lagrangian is rewritten in complex form. The resulting algebraic equations connect the complex amplitudes of vibration components with the amplitudes of periodic forces at the same frequencies and the parameters of the mechanical system (stiffness, damping). The amplitudes of periodic forces are related to the magnitude of the shafts angular and parallel misalignment according to the accepted model. Calculation of intercomponent phase relations values is used to get rid of the random initial phase shift caused by the choice of the timing reference. The magnitude of the effect produced by the misalignment of the shafts on the amplitudes and values of the intercomponent phase relations of the signal components is estimated. The obtained resultcan be used to construct devices for estimation shaft displacements and devices for assessing the condition of equipment based on the analysis of vibration signals.ls.